2017
DOI: 10.1016/j.virusres.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β response is impaired by hepatitis B virus infection in Tupaia belangeri

Abstract: To date, the chimpanzee has been used as the natural infection model for hepatitis B virus (HBV). However, as this model is very costly and difficult to use because of ethical and animal welfare issues, we aimed to establish the tupaia (Tupaia belangeri) as a new model for HBV infection and characterized its intrahepatic innate immune response upon HBV infection. First, we compared the propagation of HBV genotypes A2 and C in vivo in tupaia hepatocytes. At 8-10days post infection (dpi), the level of HBV-A2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In addition, we also observed modulation of cytokines/chemokines in DENV-infected Tupaia cells, suggesting the involvement of these innate immune components in DENV infection, similar to that observed in human infections [34][35][36]. A recent study [37] demonstrated that DENV could activate a cGAS response and in an in vitro study of DENV infection we detected the expression pattern of cGAS in the sample from a previous study [24], as described [16]. We observed that DENV serotype 1, but not other serotypes, significantly upregulated cGAS mRNA expression 72 h post-infection in Tupaia cells (Figure 1).…”
Section: Dengue Virus (Denv)supporting
confidence: 77%
See 4 more Smart Citations
“…In addition, we also observed modulation of cytokines/chemokines in DENV-infected Tupaia cells, suggesting the involvement of these innate immune components in DENV infection, similar to that observed in human infections [34][35][36]. A recent study [37] demonstrated that DENV could activate a cGAS response and in an in vitro study of DENV infection we detected the expression pattern of cGAS in the sample from a previous study [24], as described [16]. We observed that DENV serotype 1, but not other serotypes, significantly upregulated cGAS mRNA expression 72 h post-infection in Tupaia cells (Figure 1).…”
Section: Dengue Virus (Denv)supporting
confidence: 77%
“…In addition, Ruan et al demonstrated the similarities of pathological changes in HBV-infected Tupaia liver tissues with the disease progression in humans [61]. In a recent study, we found that the establishment of chronic HBV infection and an impaired IFN-β response could be caused by the HBV-A2 genotype in the Tupaia infection model [16]. On the other hand, during acute infection, impaired IFN-β response was only observed in HBV-A2_JP4-infected Tupaia, but not in HBV-A2_JP1-infected Tupaia, which is suggestive for the role of IFN-β suppression towards the establishment of chronicity in the Tupaia model of HBV infection [16].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 58%
See 3 more Smart Citations